Skladenjske posebnosti slovenščine v razmerjih glagol – vezljivost – stavčni vzorec - Žele, Andreja (Slavia Centralis, 2020)
Syntactical Peculiarities of Slovenian in Verb, Valency and Sentence Pattern Relations The paper presents some of the syntactical peculiarities of Slovenian that are reflected in the relation between valence capabilities of certain verbs and sentence patterns that are possible in the Slovenian language. In connection with this we also discuss specific characteristics of certain participants and their participant roles that on the expressive level are reflected in relations between adverbial valency and obligatory complements.